THE INTERFACE BETWEEN CHILD GROWTH AND ACTIVE METHODOLOGIES IN THE CHILD AND ADOLESCENT HEALTH COURSE: AN EXPERIENCE REPORT - Victor Lucas Dutra de Morais; Vinícius Luan Dutra de Morais; Ingridi Eduarda Galdino da Silva; Simone Souza de Freitas (Artefactum - revista de estudos interdisciplinares, 2026)
This study examines the intersection between child growth and the use of active methodologies in teaching the course on Child and Adolescent Health. Its objective was to report on the experience of applying innovative pedagogical strategies in the teaching-learning process, with a view to fostering critical and reflective thinking among health students. This is a descriptive study, in the form of an experience report, conducted in an academic setting, in which active methodologies, such as an integrated panel and the “Growth Tree,” were used. The results showed greater student engagement, the development of critical thinking, and a better understanding of aspects related to child growth and development. In addition, an increase in student autonomy and greater integration between theory and practice were observed. It is concluded that the use of active methodologies contributes to the quality of education in the health field, fostering the training of professionals who are better prepared to provide comprehensive and humanized care for children and adolescents.